Death of an avatar: Implications of presence for learners and educators in virtual worlds. Issue 2 (14th September 2012) - Ferguson, Rebecca
Virtual worlds such as Second Life® offer learners and educators environments in which they can engage in activities that would be too difficult, dangerous or impossible in the physical world. Increasingly, these settings provide learners with a sense of presence – an impression that their mediated presence is not mediated. Presence includes realistic representations, sophisticated social interaction and immersive experiences. What are the implications for learners when death is introduced into an immersive, but apparently safe and protected, educational environment? To answer this question, this article draws on a virtual ethnographic study carried out over four years in Second Life and Teen Second Life™. It finds that there are different types of death within Second Life, some permanent and some transient, some wholly virtual, others reflecting a situation in the physical world. Analysis of the theme of death in different settings and subject categories shows that learners and educators make use of some of these types of death to help with exploration of subjects as diverse as Roman history, military training and classic literature. In order to make use of these types of death, educators vary levels of realism, immersion and social interaction, thus altering the levels of presence available within an environment. Other types of Second Life death are not typically explored in educational settings but nevertheless raise a series of legal, social and ethical issues that will need to be addressed by future curricula.